Structural and contextual hurdles to opposition party success in Namibia: the role of strategic dilemmas and political rhetoric - Weylandt, M (2015)
Ever since the third wave of democratisation swept the continent, Africa's opposition parties have been conspicuous by their poor performance. In explaining this weakness, the literature usually points to the disparity in resources and other incumbency benefits as well as narrow support bases of these parties. While these factors help explaining the poor performance of Namibia's opposition, they do not offer a full account. This thesis argues that strategic dilemmas arising from Swapo's electoral dominance, in interaction with a powerful historical narrative driven by the ruling party, make it harder for opposition parties to build sustainable, broad movements. Swapo's dominance means that voters think challengers are unviable and thus will not engage in strategic voting; it means that coalitions are unlikely because opposition party leaders see no point in putting differences aside; and it means that ruling party elites are unlikely to dissent. All of these tendencies are fortified by Swapo's powerful usage of political rhetoric. As the party that is credited with bringing about liberation from colonialism, Swapo draws upon a powerful well of legitimacy. The historical narrative it promotes reinforces these strategic dilemmas by painting Swapo as the only rightful representative of the Namibian people and labelling dissent as unpatriotic. The party also makes astute usage of rhetoric in the realm of ethnic politics, where it has forced all parties to adopt a form of diversity that is hard to manage with meagre resources. Thus, contrary to the stance of much of the literature on African politics, ideas matter.